Geochemical Recharge Estimation and the Effects of a Declining Water Table. Issue 10 (29th September 2016) - Katz, Britney S.; Stotler, Randy L.; Hirmas, Daniel; Ludvigson, Greg; Smith, Jon J.; Whittemore, Donald O.
Abstract : Core Ideas: Intensive groundwater development has led to steep water‐level declines. Geochemically, vadose zone water in drained zone is identical to groundwater. Geochemical estimates of recharge rates not possible through this drained zone. With steep water‐level declines, care is needed for geochemical recharge estimates. In this area, focused recharge likely dominates over diffuse recharge. The High Plains aquifer (HPA) is one of the largest aquifers in the world and is critical for agricultural production in the United States. In Kansas, irrigation using the HPA has resulted in steep groundwater declines. Unexpected water‐level response to pumping recovery in the northwestern Kansas portion of the HPA was recently observed, indicating a previously unknown source of recharge. The goal of this research was to investigate water movement and vadose zone chemical inventories to constrain recharge pathways and rates to the aquifer. Detailed geochemical profiles at a cored site indicated displaced chloride, bromide, nitrate–nitrogen (NO3 –N), and sulfate reservoirs—likely mobilized by the onset of on‐site irrigation—believed to have commenced in 1984. Water in the vadose zone beneath the predevelopment water table (36–63 m below ground surface) is remnant groundwater left as the water table declined. Thus, assumptions of a chloride mass balance are not valid in this zone. These results indicate irrigation return flow has yet to travel through the vadose zone to recharge the aquifer at this location. Calculated chemical transit times through the profile to the predevelopment water table exceed the start of irrigation at the site, and groundwater radiocarbon ages on the order of 3000 yr BP provide further evidence against substantial irrigation return to the aquifer. These data establish evidence for complicated flow paths through the vadose zone to the aquifer and argue against broad, diffuse recharge to the aquifer. Future studies in the area should investigate focused recharge pathways to identify recharge sources.